Nationalization and Expropriation: States’ Right - Chobanyan, G. (Bulletin of Yerevan University C: Jurisprudence, 2020)
The article is devoted to the issues of state rights on expropriation and nationalization in the frameworks of international investment law. Particularly, the article addresses the concepts of nationalization and expropriation, as well as the main conditions for the right to expropriate. The article discusses the differences of lawful and unlawful expropriations. The author tried to show that there are certain criteria state should meet for lawful expropriation.
Keywords: expropriation, nationalization, economic sovereignty, foreign investments, investment law